Antiplatelet Effects of Flavonoids Mediated by Inhibition of Arachidonic Acid Based Pathway - Karlíčková, Jana; Říha, Michal; Filipský, Tomáš; Macáková, Kateřina; Hrdina, Radomír; Mladěnka, Přemysl (Planta medica, 2016)
Flavonoids, important components of human diet, have been claimed to possess a significant antiplatelet potential, in particular due to their effects on the arachidonic acid cascade. Due to variable and incomplete results, this study was aimed at delivering a detailed analysis of the effects of 29 structurally relevant, mainly natural flavonoids on three consecutive steps of the arachidonic acid cascade.Only the isoflavonoids genistein and daidzein were shown to possess a marked cyclooxygenase-1 inhibitory activity, which was higher than that of acetylsalicylic acid using the isolated ovine enzyme, and physiologically relevant, although lower than acetylsalicylic acid in human platelets. None of the tested flavonoids possesses an effect on thromboxane synthase in a clinically achievable concentration. Contrarily, many flavonoids, particularly those possessing an isolated 7-hydroxyl group and/or a 4'-hydroxyl group, acted as antagonists on thromboxane receptors. Interestingly, the substitution of the free 7-hydroxyl group by glucose might not abolish the activity.In conclusion, the consumption of few flavonoids in a diet, particularly of the isoflavonoids genistein and daidzein, may positively influence platelet aggregation.
Keywords: kyselina arachidonová; Platelet Aggregation Inhibitors; receptory thromboxanů; Structure-Activity Relationship; Thromboxane-A Synthase; lidé; flavonoidy; thromboxan-A-synthasa; cyklooxygenasa 1; Flavonoids; Arachidonic Acid; Cyclooxygenase 1; Receptors, Thromboxane; inhibitory cyklooxygenasy; Cyclooxygenase Inhibitors; Humans; vztahy mezi strukturou a aktivitou; inhibitory agregace trombocytů